An initial carbon export assessment in the Mediterranean Sea based on drifting sediment traps and the Underwater Vision Profiler data sets. (November 2016) - Ramondenc, Simon; Madeleine, Goutx; Lombard, Fabien; Santinelli, Chiara; Stemmann, Lars; Gorsky, Gabriel; Guidi, Lionel
Abstract: During the SESAME EU FP6 project, all available particulate organic carbon (POC) data collected from drifting sediment trap and Underwater Vision Profiler deployments (INSU PROOF database, 1991–2011) were gathered in order to assess carbon export at the scale of the Mediterranean Sea. In this study, we observed that particle size, POC export, and the contribution of microphytoplankton to the phytoplankton community structure, all decreased following the west to east net primary production gradient. One the other hand, no clear longitudinal gradient was found regarding particle composition (C/N ratio or lipid content). The above longitudinal patterns were also observed at the seasonal scale from spring to summer in the northwestern sub-basin. These observations suggest that particle size rather than organic matter composition controls fluxes of POC in the Mediterranean Sea. The comparison between POC and dissolved organic carbon (DOC) fluxes highlights the different time-scale of physicals vertical mechanisms and suggests that DOC flux can play an underestimated role in the supply of fresh carbon to the deep waters Mediterranean Sea. Indeed, DOC supply to deeper layers can be one order of magnitude larger than particle carbon flux but occurs in pulses when stratification breaks due to (i) deep-water formation, or (ii) winter mixing. In contrast, the vertical export of POC occurs throughout the year bringing weak, but almost continuous, energy to meso- and bathypelagic organisms. Highlights: An Initial climatology of Carbon export in the Mediterranean Sea. POC flux from PSD compared to POC flux from drifting sediment traps. POC export decrease eastward in the Mediterranean Sea. DOC contribution to carbon export is underestimated in Mediterranean Sea. Mesoscale structure impact carbon export.